Evaluasi Sistem Pembelajaran Pendidikan Agama Islam Menggunakan Model CIPP untuk Meningkatkan Indeks Pembangunan Manusia di SDN Banjaran 2 Kota Kediri: Evaluasi Sistem Pembelajaran Pendidikan Agama Islam Menggunakan Model CIPP untuk Meningkatkan Indeks Pembangunan Manusia di SDN Banjaran 2 Kota Kediri - Arina Qak; Izza Shofiana (The Elementary Journal, 2026)
This study aims to analyze and evaluate the implementation of Islamic Religious Education (IRE) instruction using the CIPP model (Context, Input, Process, Product) as an effort to improve student quality, thereby contributing to the Human Development Index (HDI) at SDN Banjaran 2 in Kediri City. The CIPP evaluation model is one of the program evaluation approaches developed by Stufflebeam that is oriented toward decision-making and the continuous improvement of program quality. This study employs a descriptive qualitative approach with data collection techniques including in-depth interviews, observations, and document analysis. The research results indicate that in the context dimension, the PAI learning objectives are aligned with the institution’s vision of shaping students with religious character who can internalize Islamic values in their daily lives. In the input dimension, teacher readiness, curriculum implementation, and the availability of facilities and infrastructure are considered adequate, although there is still a need to optimize the use of learning media and strengthen parental involvement. In the process dimension, learning activities took place quite effectively through the application of varied methods combined with the reinforcement of religious practices, such as reciting the Asmaul Husna, performing the Dhuha prayer, and reciting short surahs before lessons began. In terms of the product dimension, improvements were observed in students’ cognitive, affective, and psychomotor aspects, as reflected in their religious understanding, attitudes, and religious practices. Thus, it can be concluded that the implementation of Islamic Education (PAI) instruction based on the CIPP model makes a significant contribution to improving student quality, particularly in supporting the educational dimension of the Human Development Index (HDI).